Pemanfaatan ChatGPT untuk Meningkatkan Kemampuan Berbahasa Inggris Siswa SMK Terpadu Al-Islahiyah: Pendekatan Interaktif dan Inovatif - Alaydrus, Yahya; Hidayanti, Ika; Kurniasih, Kurniasih; Nasihah, Durotun; Umamah, Atik; Nugroho, Mochammad Khosy Xavier; Oktavia, Fathia Afray Vita (Jurnal SOLMA, 2025)
Background: This community service activity was carried out to address the problems faced by students in improving their English proficiency. Method: To solve these problems, the service team conducted a training/workshop by utilizing Artificial Intelligence (AI), namely ChatGPT. The activity began with a pre-workshop survey distributed to 45 students of SMK Terpadu Al-Islahiyah Singosari, majoring in Office Management, to identify their problems and confidence level. It was followed by the Implementation and Evaluation Stages through a post-training survey and interviews with the English teacher. Results: Data analysis showed that students experienced difficulties in learning English due to limited vocabulary, pronunciation challenges, and lack of confidence. In addition, their confidence level increased from mostly fairly confident to highly confident. The English teacher also gave a positive perception of the implementation of ChatGPT while reminding the need to anticipate its potential negative impacts. Conclusion: Based on these findings, it can be concluded that AI plays an important role in language learning through the active role of teachers in monitoring, so that technology can be utilized properly and responsibly.